2011
DOI: 10.1097/aog.0b013e31822a65e4
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Volume, Provider Volume, and Complications After Childbirth in U.S. Hospitals

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 16 publications
4
54
1
Order By: Relevance
“…On the basis of their definition of maternal complications, which included: haemorrhage, laceration, infection, and thrombotic complications, the authors found an adjusted complication rate of 15% in the first year following residency, which is within the range of what has been observed in previous large-scale studies using discharge data1 and a consistent downward trend in complications that was steepest in the first decade, but continued throughout the first three decades of practice. The trend was robust to a variety of different analytic techniques and subgroup analyses.…”
Section: Resultssupporting
confidence: 58%
“…On the basis of their definition of maternal complications, which included: haemorrhage, laceration, infection, and thrombotic complications, the authors found an adjusted complication rate of 15% in the first year following residency, which is within the range of what has been observed in previous large-scale studies using discharge data1 and a consistent downward trend in complications that was steepest in the first decade, but continued throughout the first three decades of practice. The trend was robust to a variety of different analytic techniques and subgroup analyses.…”
Section: Resultssupporting
confidence: 58%
“…11,14 Relevant maternal comorbidities, pregnancy complications, deliveryrelated procedures, and intrapartum complications were identified using the diagnosis and procedure codes from the International Classification of Diseases, Ninth Revision (ICD-9), listed in Appendix A. Comorbidities and complications were classified using previously described algorithms for identifying reliable pregnancy-related data using ICD-9 codes. [15][16][17] Available maternal characteristics included for comparison were age, race/ethnicity, primary insurance payer, median household income (in quartiles based on a patient's postal code), and maternal comorbidities. Pregnancy characteristics included multiple gestation, prior cesarean delivery, presence of preterm labor, and placental previa (encompassing all abnormal placentations).…”
Section: Methodsmentioning
confidence: 99%
“…One prior study using the National Inpatient Sample found no consistent association between hospital obstetric volume and maternal complications. 9 In contrast, one study found increased rates of adverse maternal outcomes in very low-volume hospitals, and in the highest-volume hospitals for cesarean deliveries; 10 another study found increased rates of obstetric infection in teaching hospitals and hospitals with higher numbers of beds. 7 Several design and analysis differences could explain these differences: different study populations/states, modeling approaches, and outcome definitions.…”
Section: Commentmentioning
confidence: 95%